Activation of persulfate by biochar for the degradation of phenolic compounds in aqueous systems - Kleopatra Miserli (Elsevier, 2022)
Advanced Oxidation Processes (AOPs) based on sulfate radicals (SR-AOPs) are efficient chemical methods for water and wastewater treatment gaining attention in the last years. In this study, the application of biochar (BC) matrix as an alternative carbon catalyst for the activation of persulfate (PS) and degradation of phenol and phenolic transformation products was examined. BC/PS system was compared with BC/Fe2+/PS system however the presence of Fe2+ did not enhance greatly the degradation rate showing that biochar playing the major role in PS activation. The effect of various parameters, such as PS and BC dosing, pH, the presence of anions (Cl−, NO3−, HCO3−, HPO42−) and humic acids (HA), separately and in combination, at different concentration levels, simulating surface waters and wastewaters, in degradation kinetics was studied. Degradation of phenolics followed pseudo-first order kinetics in all cases and under optimum conditions, fast complete removal was achieved within few minutes. The presence of all anions studied decreased the removal rate of phenolics with HPO42− showing the greater inhibition. Moreover, humic acids, as representatives of natural organic matter (NOM), decrease phenolics degradation efficiency and in combination with anions showed the more pronounced inhibitory effect. In addition, scavenger quenching experiments with ethanol, tert-butanol and NaN3 confirmed the dominant role of 1O2 following by HO• radicals while sulfate (SO4•−) radicals contribute to a minor degree. Biochar loses progressively its activation efficiency after three cycles. The results of this study contribute to the development of analogous treatment technologies for the removal of phenol-based taste and odor compounds.